ANALISIS STANDAR PENILAIAN PENDIDIKAN - Barnawi Barnawi; Didik Himawan; Sopyan Sauri; Ujang Cepi Barlian (Lembaga Publikasi Ilmiah, 2022)
Educational Assessment Standards are part of the National Education Standards (SNP), which are a form of elaboration of the mandate of Law Number 20 of 2003 concerning the National Education System. An educator must understand educational assessment standards, and understand the juridical basis behind the assessment standards, evaluation mechanisms, and procedures. Existing legal products related to educational assessment have regulated the mechanism, form and instrument of educational assessment. By understanding the juridical basis related to educational assessment, then at least an educator participates in delivering standardized quality education, so that the goals of education in Indonesia can be realized. ABSTRAK Standar Penilaian Pendidikan merupakan bagian dari Standar Nasional Pendidikan (SNP), dimana bentuk penjabaran dari amanat Undang-Undang Nomor 20 Tahun 2003 tentang Sistem Pendidikan Nasional. Seorang pendidik harus memahami standar penilaian pendidikan, dan memahami landasan yuridis yang melatarbelakangi standar penilaian, mekanisme, dan prosedur evaluasi. Produk hukum yang ada terkait penilaian pendidikan, telah mengatur bagaimana mekanisme, bentuk, instrumen penilaian pendidikan. Dengan memahami landasan yuridis terkait dengan penilaian pendidikan, maka setidaknya seorang pendidik ikut peran serta mengantarkan mutu pendidikan yang sudah terstandarisasi, sehingga tujuan dari pendidikan di Indonesia dapat terwujud.